Introduction to Tensorflow - Ketkar, Nikhil (Deep Learning with Python, 2017)
In this chapter we will cover Tensorflow which allows users to define mathematical functions via computational graphs and to compute their gradients. Tensorflow is conceptually similar to Theano, and Keras uses both of them as back ends.